EVALUASI PENGGUNAAN ALOKASI DANA DESA DALAM PEMBANGUNAN DESA DI KECAMATAN TELUK PANDAN KABUPATEN KUTAI TIMUR - Kusuma, Aji Ratna (Jurnal Administrative Reform, 2017)
This article aim to explain ho the evaluation result from the utilization of village fund in Teluk Pandan sub-district. Using qualitative method, this article describe the result in analytical fashion. The result shows that the utilization of village fund in Teluk Pandan sub-district is allocated mostly in infrastructure, society’s empowerment and poverty program.